2003
DOI: 10.1034/j.1398-9995.2003.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low dose fluticasone/salmeterol combination on surrogate inflammatory markers in moderate persistent asthma

Abstract: Surrogate markers apart from serum ECP may be used as a guide to evaluate the anti-inflammatory effects of low dose inhaled corticosteroids. Sputum markers tend to be more sensitive than blood when assessing the anti-inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
2
15
0
1
Order By: Relevance
“…However, only moderate correlations have been reported between the 2 components, 8 and this view is now being challenged by a model in which systemic inflammation plays an independent role in patients with asthma and other respiratory diseases. 3,9,10 This new hypothesis is supported by data from studies showing that systemic inflammation is not always reduced by inhaled corticosteroids 11,12 and that systemic therapies, such as leukotriene receptor antagonists, might be more effective in reducing systemic inflammatory markers. 13,14 Furthermore, biological treatments directed at blocking IL-5 effectively decrease the signs of systemic inflammation, as measured by B-Eos values, but does not change FENO values, 15 whereas anti-IL-13 treatment reduces FENO values without decreasing B-Eos values.…”
supporting
confidence: 57%
“…However, only moderate correlations have been reported between the 2 components, 8 and this view is now being challenged by a model in which systemic inflammation plays an independent role in patients with asthma and other respiratory diseases. 3,9,10 This new hypothesis is supported by data from studies showing that systemic inflammation is not always reduced by inhaled corticosteroids 11,12 and that systemic therapies, such as leukotriene receptor antagonists, might be more effective in reducing systemic inflammatory markers. 13,14 Furthermore, biological treatments directed at blocking IL-5 effectively decrease the signs of systemic inflammation, as measured by B-Eos values, but does not change FENO values, 15 whereas anti-IL-13 treatment reduces FENO values without decreasing B-Eos values.…”
supporting
confidence: 57%
“…Nevertheless, some studies claimed that sputum markers may be more sensitive than blood when assessing the anti-inflammatory response in asthma. 37 In conclusion, this is the first study to investigate the effects on allergen-induced bronchial inflammation from adding salmeterol to fluticasone in patients with asthma. We have shown that a single dose of salmeterol in a combination inhaler with fluticasone has an additional effect on serum IL-5 concentrations and eosinophil counts in peripheral blood after allergen challenge in vivo in patients with allergic asthma, complementary to the effect of a single dose of fluticasone alone.…”
Section: Discussionmentioning
confidence: 97%
“…The relative suppression of eosinophils and ECP in response to 400ug/day beclometasone equivalent ICS dose is 23% and 17% respectively for blood and 76% and 55% for sputum, 6 inferring that sputum is more sensitive, although it is less practical. In this regard it has been shown that titrating ICS against sputum eosinophils results in reduced exacerbations and associated AHR.…”
Section: To the Editormentioning
confidence: 99%